2016
DOI: 10.1111/fare.12183
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Formal and Informal Support on Health in the Context of Caregiving Stress

Abstract: Caregiving stress increases risk for poor health. The overproduction of inflammatory markers is a core process contributing to this effect. In this study the authors investigated whether formal and informal social support act as protective factors against stress‐induced immune dysregulation. Fifty‐six parents of children with an autism spectrum disorder completed questionnaires on formal support services, informal social support, self‐rated health, and daily somatic symptoms, and they provided a blood sample f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 98 publications
(132 reference statements)
3
28
0
9
Order By: Relevance
“…Despite these limitations, the findings from this review add to the body of literature demonstrating that BPT and CSIs serve as productive means of providing formal social support to parents of children with a DD. Previous research has found that higher levels of social support, formal and informal, are related to lower levels of reported stress and improved response (physiological and emotional) to stressors (Gouin et al, ; Mezuk et al, ; Perry, ). Furthermore, Gouin et al () found that these decreases in parents' immune dysregulation (and corresponding somatic symptoms), related to levels of social support, increase with the children's age.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Despite these limitations, the findings from this review add to the body of literature demonstrating that BPT and CSIs serve as productive means of providing formal social support to parents of children with a DD. Previous research has found that higher levels of social support, formal and informal, are related to lower levels of reported stress and improved response (physiological and emotional) to stressors (Gouin et al, ; Mezuk et al, ; Perry, ). Furthermore, Gouin et al () found that these decreases in parents' immune dysregulation (and corresponding somatic symptoms), related to levels of social support, increase with the children's age.…”
Section: Discussionmentioning
confidence: 97%
“…Previous research has found that higher levels of social support, formal and informal, are related to lower levels of reported stress and improved response (physiological and emotional) to stressors (Gouin et al, ; Mezuk et al, ; Perry, ). Furthermore, Gouin et al () found that these decreases in parents' immune dysregulation (and corresponding somatic symptoms), related to levels of social support, increase with the children's age. This finding has significant implications given the natural tendency for inflammatory markers to increase with age (Michaud et al, ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The scientific literature abounds with information on cognition and memory changes among older populations (Grady, ), demographic trends (Markle‐Reid et al, ), implications of exceptional longevity, and the ever‐present reminder that the provision of care to loved ones is extraordinarily demanding (Bastawrous, , Evans & Lee, ; Gouin, de Estrela, Desmarais, & Barker, ; Martire, Stephens, & Schultz, ; Qualls, ; Roberto et al, ). Much has also been written about the theoretical and practical applications of resilience among individuals and families across the life course (Johnston, Bailey, & Wilson, ; Roush et al, ; Verbeek, Kane, van Rossum, & Hamers, ).…”
mentioning
confidence: 99%